Potential of epoxidized natural rubber (ENR) as hydrophobicity contributor in chitosan-urea fertilizer - Mohamad, Noraiham; Abdul Hamid, Nor Nadiah; Abdul Aziz, Nor Abidah; Abd Razak, Jeefferie; Azlan, Umar Al-Amani; Dimin @ Mohd Amin, Mohd Fairuz; Shaaban, Azizah (Trans Tech Publications, 2014)
Abstract. This study is to investigate the potential of ENR to be incorporated with chitosan for slow release urea fertilizer. In this research, mixture of chitosan and epoxidized natural rubber (ENR) was used as binder to take advantage of their biodegradable and polar characteristics, respectively. The effect of mixing formulation to the properties of fertilizer was studied. Firstly, the chitosan and ENR were diluted in toluene with the presence of bentonite as filler. Then, urea powder was mixed and stirred for 20 minutes before left to dry overnight in an oven at 60°C. Water absorption and water retention analysis were carried out on compressed pellets. The increase of ENR loading was observed to contribute to the increase of hydrophobic properties of the fertilizer. The findings were supported by compositional analysis using Fourier Transform Infrared spectroscopy (FTIR).